Поведінка вірусів рослин та їх комплексів на поверхні монокристала Sі (111) - Шпак, А.П.; Карбівський, В.Л.; Корніюк, Т.А. (Видавничий дім "Академперіодика" НАН України, 2008)
We use ultrahigh-vacuum atomic force microscopy (UHV - AFM) to study the interaction of tobacco mosaic virus (TMV) and alfalfa mosaic virus (AMV) with a Si (111) surface. Changes of the virion conformation and different degrees of order on the investigated surface are established. It is demonstrated that the adsorption of TMV virions is accompanied by the formation of predominantly single-layer ordered films, while the AMV adsorption is accompanied by the formation of unordered accumulations of virions and a more abrupt change of the height of viral particles. It is established that the change of virions’ height depends on the number of negativelycharged amino acid residues on the outer surface of a capsid.